Knowledge, Attitude and Practices towards Prevention of Malaria among Pregnant women aged 18-45 years at Busibo Health Centre III, Lwengo District. A Cross-section Study. - Musimenta, Catherine; Mubangizi, Prosper (Student's Journal of Health Research Africa, 2022)
Background: The purpose of the study was to assess the knowledge, attitude, and practices toward the prevention of malaria among pregnant women aged 18-45 years at Busibo health center III, Lwengo district. Methodology: A cross-section study design was employed as a study design with a simple random technique as a sampling technique. Data were collected on a sample of 50 respondents using a semi-structured questionnaire written in the English language as a data collection tool; later analyzed manually by use of tally sheets and presented in frequency distribution tables and figures. Results: Overall results from practices towards malaria prevention among pregnant mothers showed that; 50% of the respondents had attended three ANC visits, 76% had treated mosquito bed nets, 61% reported that sometimes they use the mosquito bed nets, 54% use of ITNs to prevent themselves from malaria infection, 70% maintain their mosquito bed nets by folding them every morning to prevent hoes and 88% always take IPTp. Conclusion: the study established that even though a significant number of pregnant mothers possessed fairly satisfactory knowledge, attitude, and practices towards malaria prevention but infrequent percentage number of pregnant mothers who were reluctant to uptake ANC and ITNs need extra interventions for equitable malaria prevention that will close the research gap. Recommendation; Busibo Health Centre III, Lwengo should intensively increase the awareness interventions about the dangers of untimely ANC visits and irregular use of ITNs through; health education of mothers during antenatal visits and community outreaches to implement better behavior changes that will close the research gap.